Youth Engagement in Northern Communities: A Narrative Exploration of Aboriginal Youth Participation in a Positive Youth Development Program - Callingham, Christina (Université d'Ottawa / University of Ottawa, 2015)
This qualitative study aimed to enhance our understanding of youth engagement experiences from the perspective of Aboriginal youth living in the Canadian North, as positive youth development programs can foster community engagement among youth and may have implications for Aboriginal youth involvement in community healing. With an asset-based orientation that recognizes that youths’ strengths co-exist with, and are understood in relation to, environmental challenges, narrative inquiry was used to explore the experiences of six Aboriginal youth who participated in a program that promotes community engagement. Rich participant accounts resulted in better understanding youth engagement as a profound culture-bound process rather than simple participation in a program, and illuminates the importance of positive relationships, adult support, and pre-program community involvement to building subsequent engagement. This study has implications specific to Aboriginal youth as having a role in promoting health and healing in their communities through their engagement.
Keywords: youth engagement; Positive youth development; Social justice; Narrative inquiry; Social constructionism; Aboriginal youth